Postgraduate Students’ Perceptions of English as a Medium of Instruction (EMI): Comprehension, Participation, and Language Development (ELS Journal on Interdisciplinary Studies in Humanities, 2026)
This study investigates postgraduate students’ perceptions of English as a Medium of Instruction (EMI), focusing on comprehension, participation, and academic English development. Using a mixed-method approach, data were collected from eight postgraduate students through a structured questionnaire consisting of Likert-scale and open-ended items. The findings indicate that students generally prefer an English-dominant instructional approach, ranging from 70% to 95%, while still recognizing the importance of limited Indonesian use for clarification. English-medium instruction was found to enhance students’ confidence and participation, although occasional use of Indonesian helped facilitate the expression of complex ideas. In terms of comprehension, students reported better understanding when English was used, supported by strategic code-switching. Furthermore, EMI significantly contributes to the development of academic English skills, including vocabulary, writing, and communication. Overall, a balanced and flexible approach to EMI is recommended to optimize both language development and learning effectiveness in postgraduate contexts.
Keywords: EMI; Comprehension; Participation